Guidance on the assessment of learning outcomes for those designing procedures and projects: report of an ETPLAS working group - Dontas, Ismene A.; Fry, Derek J; Lewis, David I; Applebee, Kenneth; Fentener van Vlissingen, Martje; Marinou, Katerina; Schenkel, Johannes (Laboratory animals, 2024)
This document provides assessment criteria for evaluation of each of the Learning Outcomes of the Modules specified (in addition to the Core Modules) for those designing procedures and projects in the Education and Training Framework guidance document by the European Commission and endorsed by the Member States Competent Authorities. This Working Group was tasked to produce these criteria by the Education & Training Platform for Laboratory Animal Science, which was funded by the European Commission to this aim. The assessment criteria address knowledge and skills (including critical thinking) expected to be acquired during education and training of persons preparing to design research procedures and projects using animals under the scope of Directive 2010/63/EU. Recognizing the diversity of expertise and experiences of those being educated and trained, we provide two levels of attainment, an ideal response and one that would be acceptable for each Learning Outcome. The balance between ideal and acceptable could be decided by the particular course providers and/or assessors, according to their local requirements. We envisage that the use of these assessment criteria by training providers and accrediting or approving bodies will help harmonize the education and training for those who will design procedures and projects using animals for scientific purposes. In Europe, this may also contribute to mutual recognition of training, and facilitate free movement of scientists.
Online veröffentlicht: 23. September 2024
Gesehen am 02.04.2025